Institutional entrepreneurship in the Ethiopian coffee industry. (1st January 2012) - Curtis, Timothy; Nalbandian, Raffi
This paper explores the underlying public entrepreneurship in the coffee industry in Ethiopia. It investigates the concept of political innovation in a public sector entrepreneurship agenda, in the context of work exploring the employment of entrepreneurship by the state as a economic and social development strategy in post-socialist countries such as China (Curtis, 2011) and Poland (Curtis et al., 2010). The case study confirms other research on post-socialist economies but indicates the risks of participation in commodity markets, rather than shaping long-term markets (Mazzucato, 2011), and being subjected to the turmoil of unregulated markets, rather than mastering of them.